2021
DOI: 10.1029/2020gl089163
|View full text |Cite
|
Sign up to set email alerts
|

How Equivalent Are Equivalent Porous Media?

Abstract: Fractures are ubiquitous in rock masses and control their transport and deformation properties (Cornet, 2015;Jaeger et al., 2007). On the one hand, fractures represent preferential paths for fluid flow because their permeability is usually several orders of magnitude higher than that of intact rock (Rutqvist, 2015;Witherspoon et al., 1980;Zimmerman & Bodvarsson, 1996). On the other hand, fractures represent weak planes with lower strength and higher deformability than the intact rock (Bandis et al., 1983;Barto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 74 publications
0
23
0
Order By: Relevance
“…In addition, the results of permeability measurements and stress-permeability relation are also known to be size-dependent 10 . Finally, the laboratory tests are usually conducted on specimens with one or several fractures, while the fracture network should be considered for the in-situ conditions 23 . All of these challenges need to be properly addressed before the implementation of laboratory measured properties in the reservoir-scale numerical models.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the results of permeability measurements and stress-permeability relation are also known to be size-dependent 10 . Finally, the laboratory tests are usually conducted on specimens with one or several fractures, while the fracture network should be considered for the in-situ conditions 23 . All of these challenges need to be properly addressed before the implementation of laboratory measured properties in the reservoir-scale numerical models.…”
Section: Discussionmentioning
confidence: 99%
“…However, the simulation of the hydraulic stimulation shows that pore pressure does not reach the critical pressure for most of the faults. Thus, even though pore pressure buildup has a direct effect on faults, especially in those in the vicinity of the well, other triggering mechanisms are relevant and should be taken into account to enable reliable estimates of induced seismicity 41 .…”
Section: Discussionmentioning
confidence: 99%
“…The strong contrast between fracture and matrix properties further challenges equivalent continuum models. For example, recent studies (Haagenson & Rajaram, 2021) suggest that although the propagation of spatially averaged fields (e.g., radially averaged pressure, temperature or concentration) may be accurately captured in equivalent continuum representations, propagation of high pressures and temperature perturbations, which drive stress‐dependent fracture behavior and shear slip, which are the critical elements of H‐M coupling, could be significantly misrepresented by equivalent continuum models (Zareidarmiyan et al., 2021). Again, discrete methods can more accurately capture the propagation of these high pressure and temperature perturbations since network structure is explicitly considered, as clarified in the above studies.…”
Section: Models Of T‐h‐m‐c Coupled Processes In Fractured Rockmentioning
confidence: 99%
“…Several recent modeling studies have shown that the propagation of seismic slip in fractured rock involves an apparent diffusivity (“seismic diffusivity”) that can exceed the hydraulic diffusivity by more than an order of magnitude (Haagenson & Rajaram, 2021; Zareidarmiyan et al., 2021). Given the uncertainty associated at various levels with modeling IIS, including data assimilation, T‐H‐M‐C process models, and the locations of existing faults, a general‐purpose probabilistic risk assessment framework is needed (Baisch et al., 2019; Bommer et al., 2015).…”
Section: Uncertainty Quantification Multifidelity Models and Emulatorsmentioning
confidence: 99%